Del derecho al Turismo sin escalas - Casanova Ferro, Gonzalo (2012)
In Argentina, tourism as a socio-economic activity has experienced, during the last 10 years, a formal and sustained growth beyond all circumstances. The present paper is intended to show the dual professional journey made by teachers who have started as lecturers of the legal topics contained in Tourism courses of study to finally get to explain the tourism phenomenon to the future law practitioners. During this tour or roundtrip we had to learn and unlearn various ideas or concepts in order to achieve a teaching/learning experience that was satisfying and enriching for both students and professors. Indeed, such personal experience could not be understood if not contextualized within the framework of the positive growth of the subject and of how it has been reflected in the different sources of law.